The Convergence of Human Resource Management and Artificial Intelligence: Practical Applications and Ethical Dilemmas - JENEI, Szonja; SZÉLES, Richárd; NAGY, Róbert; MOLNÁR, Judit; MORENO-GARCÍA, Elena; DÁVID, Lóránt DÉNES; KASZNÁR, Attila (Journal of Cultural Analysis and Social Change, 2025)
The application of artificial intelligence (AI) has become one of the most significant innovations in human resource management (HRM) today, fundamentally transforming the practices of recruitment, performance management, employee experience, and knowledge management. The aim of this study is to explore the organizational, technological, and psychological factors involved in the integration of AI into HR processes and to examine the attitudes and perceptions of managers, HR, and IT experts. The research was conducted using a mixed-methods approach: quantitative analysis using Spearman correlations identified significant relationships between the perceived effects of AI, while qualitative, semi-structured interviews provided deeper insight into the practical challenges of implementation. According to the results, respondents primarily associate the use of AI with improvements in efficiency, innovation, and work-life balance, while expressing particular concern about data security, ethical use, and employee trust. Based on interviews with managers and IT experts, the key to successful implementation is gradual integration, employee training and involvement, and a reliable technological infrastructure. The novelty of the research lies in its interdisciplinary approach, which combines technological, human, and organizational perspectives. The results contribute to the scientific and practical foundation for the ethical and sustainable implementation of AI-based HR systems.